Kerukshahan Meninggalkan Shalat Jum’at Pada Hari Raya Idain (Studi Takhrij Hadis) - Edriagus Saputra; Zakiyah Zakiyah; Dian Puspita Sari (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to determine the quality of the hadith about Islamic remission of leaving Friday prayer in coincidence with Eid al-Fitr or Eid al-Adha, both from the sanad and matan. This study is also to find out the hadith’s meanings. By means of takhrij al-hadith and fiqh al-hadith methods, it is concluded that the hadith about Islamic remission of living Friday prayer in coincidence with the 'Idain is dhaif because the sanad, Iyas bin Ramlah and Israil got jarah of the Muslim scholars in all channels of the hadith’s sanad. Meanwhile, for the understanding of Muslim scholars about the Islamic remission of leaving Friday prayer on the 'Idain, it is permissible as long as there are certain syar'i cases causing not to be able to perform Friday prayer, such as: rainy days, sickness, travelers, or being in the domicile far from the places that hold Friday prayer